Gas Emissions from Mixed Coal-Biomass Derived Fuel Burned in an Industrial Boilers - Annita Nurhayati (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2021)
Textille industry consumes huge amount of coal to operate their boiler. At the same time, the company generated huge amount of bottom ash from the boiler operation and it is considered as hazardous waste. PT. X has been attempting to reuse bottom ash mixed with solid waste compost to generate biofuel named as biomass coal fuel (BCF) briquettes as co-fuel for boiler combustion. This study conducted two boiler combustion experiments: i) co-firing boiler operation with 90% coal and 10% of BCF, and ii) 100% of coal. The SO2 and NO2 emissions were measured from the two experiments. The emission test was carried out using the MRU Optima 7 which is equipped by an electrochemical sensor, combined with an extraction probe to be inserted into the stack. From the emission test results, the SO2 concentration of 100% of coal burning was 150 mg/Nm3. SO2 concentration of coal fuel with a substitution of 10% BCF was 498.8 mg/Nm3. The NO2 concentration from 100% coal combustion was 174.2 mg/Nm3 while from mixed fuel combustion was 370.3 mg/Nm3. Using BCF as an aggregate for coal combustion did not bring in lower emissions of SO2 and NO2. Emission factor for SO2 from 100% coal combustion is 6.295 g/kg while for coal fuel with a substitution of 10% BCF is 31.09 g/kg. NO2 emission factor from 100%, coal burning is 7.31 g/kg while the emission factor of NO2 in coal fuel with a substitution of 10% BCF is 23.31 g/kg.